The Clinical Pharmacology and Pharmacokinetics of Ulipristal Acetate for the Treatment of Uterine Fibroids. (April 2015) - Pohl, Oliver; Zobrist, R. Howard; Gotteland, Jean-Pierre
Uterine fibroids are benign hormone-sensitive tumors of uterine smooth muscle cells leading to heavy menstrual bleeding and pelvic pain. Ulipristal acetate (UPA) is an emerging medical treatment of fibroids with the potential to be used for long-term treatment. In this context, the present article summarizes UPA's main clinical pharmacology and pharmacokinetic (PK) properties. Ulipristal acetate has good oral bioavailability and a half-life allowing one single oral administration per day for the management of fibroids. As a steroid, UPA is a substrate for cytochrome P450 (CYP) 3A4 but does not act as an inducer or inhibitor of the CYP system or transporter proteins. With the exception of drugs modulating CYP3A4 activity, risks of drug–drug interactions with UPA are unlikely. In conclusion, besides its pharmacodynamic characteristics, UPA shows favorable PK properties that contribute to a good efficacy–safety ratio for the long-term management of uterine fibroids in clinical practice.